Effect of Mikania glomerata (Asteraceae) leaf extract combined with anti-venom serum on experimental Crotalus durissus (Squamata: Viperidae) envenomation in rats - Rafael Stuani Floriano; Rosa Maria Barilli Nogueira; Michiko Sakate; Cecília Braga Laposy; Yudney Pereira da Motta; Fabíola Sangiorgio; Heloísa Costa David; João Marcelo Nabas (Revista de Biología Tropical, 2009)
Crotalic envenomation represents the highest number of deaths when compared to other snakebite envenomations of medical interest. Crotalic venom has important characteristics such as neurotoxicity, myotoxicity, nephrotoxicity, and clotting and hemolytic action. We evaluated the clinical and laboratory aspects of Crotalus durissus terrificus experimental envenomation in Wistar rats treated with antivenom and the aqueous extract of the plant Mikania glomerata. The animals were divided into three groups: Group C (control); Group VS-venom and antivenom; Group VSM-venom, antivenom and aqueous extract of M. glomerata. Crotalic poison caused clinical and laboratory alterations in Wistar mice. Significant linical alterations were: temperature decrease, edema in the venom inoculated member, sedation and a locomotion decrease in groups VS and VSM when compared with group C. A faster recovery from sedation was observed only for animals of group VSM when compared to VS. There was an increase in the number of leukocytes, neutrophils and creatine kinase in the VS and VSM groups, compared to group C. Wistar rats showed a high resistance to crotalic venom. Additional studies with different doses, time of treatment, different administration methods and histopathological and immunological studies are necessary to understand the action of M. glomerata in crotalic accidents. Rev. Biol. Trop. 57 (4): 929-937. Epub 2009 December 01. El envenamiento crotálico representa el número más alto de muertes cuando es comparado con envenenamientos por mordeduras de otras serpientes de interés médico. El veneno crotálico tiene importantes características de acción neurotóxica, miotoxicidad, nefrotoxicidad, coagulación y acción hemolítica. Este trabajo evaluó los aspectos clínicos y de laboratorio del envenenamiento experimental con el veneno de la serpiente Crotalus durissus terrificus en las ratas Wistar tratadas con suero antiofídico y extracto acuoso de M. glomerata. Los animales fueron separados en tres diferentes grupos: grupo control (C); grupo veneno+suero (VS), grupo veneno+suero+extracto acuoso de M. glomerata (VSM). El veneno crotálico causó alteraciones clínicas y diferencias en los análisis sanguíneos practicados a los ratones Wistar evaluados. Las alteraciones clínicas más importantes fueron una disminución de la temperatura, edema en el miembro inoculado de veneno, la sedación y una disminución de la locomoción en los grupos VS y VSM comparado con el grupo C. Una rápida recuperación de la sedación estadísticamente significativa fue observada en los animales del grupo VSM al compararse con los del grupo VS. Los análisis sanguíneos mostraron un aumento en el número de leucocitos, neutrofilos y creatina quinasa en los grupos VS y VSM comparados con el grupo C. Los ratones Wistar mostraron una alta resistencia al veneno del crótalo. Estudios adicionales con variación en las dosis, tiempo de tratamiento, y métodos de administración, así como la realización de estudios histopatológicos e inmunológicos son importantes para comprender la acción de M. glomerata en accidentes crotálicos.